Graduate Students and Teaching: Are We Preparing Future Adult Education Professors to Teach? - Catherine A. Cherrstrom; Dominique T. Chiup (Adult Education Research Conference, 2012)
What do we know about how graduate students are being prepared to teach? The purpose of this roundtable is to present findings from a research study and a model for graduate student professional development related to teaching. We also seek participant contributions and feedback.
Keywords: graduate student; professional development; teaching